ประสิทธิผลของการใช้โปรแกรมฝึกความจำในผู้สูงอายุที่มีภาวะสมองเสื่อมระยะแรกในคลินิกความจำ โรงพยาบาลลำปาง - รัชนี ศรเจียงคำ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Early-stage dementia is a common health problem among the elderly. The first and most prominent symptom of early-stage dementia is recent memory loss. Regular memory training can improve recent memory loss and delay memory loss of the elderly. This operational study implemented the memory training program of Wilaiwan Chaiwong (2005) and applied the implementation model guidelines from the Ontario Nurses' Association of Canada (Registered Nurses Association of Ontario [RNAO], 2012). The population of this study was a health care team of 5 people including; 1 doctor, 2 nurses, 1 psychologist and 1 patient helper. A sample group of 30 elderly people was purposively recruited and divided into two groups; 15 elderly received the memory training program and 15 who did not received the program. The research instruments comprised of the demographic data recording form for elderly with early-stage dementia and health care team, a memory scale, and satisfaction questionnaire to measure elderly with early-stage dementia and the health care team’s satisfaction of program implementation. The effectiveness of the memory program was evaluated through the memory level of the elderly with early-stage dementia on the first day and at 2 weeks, compared with the elderly with early-stage dementia who did not receive the program.